A Property of Azarin's Limit Set of Subharmonic Functions - Chouigui, A.; Grishin, A. F. (Журнал математичної фізики, аналізу, геометрії, 2008)
Let $v(z)$ be a subharmonic function of order $ρ>0$, and $Fr(v)$ be the limit set in the sense of Azarin. Let $z$ be fixed and $I(z)=\{u(z):u\in Fr(v)\}$. We prove that $I(z)$ is either a closed interval or a semiclosed interval which does not contain its infimum. Mathematics Subject Classification: 31A05.